Global aspects of (0,2) moduli space: toric varieties and tangent bundles - Donagi, Ron; Lu, Zhentao; Melnikov, Ilarion V. (Communications in mathematical physics, 2015)
We study the moduli space of A/2 half-twisted gauged linear sigma models for NEF Fano toric varieties. Focusing on toric deformations of the tangent bundle, we describe the vacuum structure of many (0,2) theories, in particular identifying loci in parameter space with spontaneous supersymmetry breaking or divergent ground ring correlators. We find that the parameter space of such an A/2 theory and its ground ring is in general a moduli stack, and we show in examples that with suitable stability conditions it is possible to obtain a simple compactification of the moduli space of smooth A/2 theories.
Gesehen am 21.03.2018